Canada : what it is, what it can be - Martin, Roger L. (University of Toronto Press, 2012)
Written in an accessible style that helps general readers understand complex economic concepts, Canada: What It Is, What It Can Be exposes the myths currently guiding our public policy, and provides ground-breaking new approaches for realizing our full prosperity potential.